Tracer Alumni berbasis Website (Kasus : Sistem Komputer Fakultas Teknik UNDIP) - Teguh Martono, Kurniawan (Jurnal Sistem Komputer, 2013)
Abstract— Alumni is one part of being an educational institution. The presence of alumni on the current one part in the assessment of accreditation an institution. By knowing where alumni of the institution to measure the extent of success in educating up to ready to work. To find out where the alumni can use the survey mentode often or by using the questionnaire that will be distributed during one pass, or by using other media that can be used to track the whereabouts of alumni. The development of information technology that exists today can play a role in supporting the search alumni. The role will involve is to make it easier for interested parties are concerned educational institutions, alumni, and stakeholeder. One of the use of information technology is to utilize the Internet network. By utilizing this network the system is built to connect globally, so it will be easier when going to access information on the alumni or feedback. The results obtained from this study is an alumni of tracer application that can be used to track the whereabouts of alumni. The system can run well on multiple web browsers. Web browsers are used in this test is by using Internet Explorer, Mozilla, Opera and Chrome. Keywords: Alumni Tracer, PHP, Information Technology